Psychological support interventions and their impact on the quality of life of persons with disabilities and their families in the United Arab Emirates - Alketbi, Hamda; Alomosh, Ahmad; Sallam, Ahmed (Al-Adab Journal, 2025)
The study aimed to investigate the types of psychological support interventions commonly used for people with disabilities and their families in the United Arab Emirates (UAE). It sought to determine the effectiveness of these psychological support interventions on the well-being and quality of life of people with disabilities in the UAE. Additionally, the study examined the impact of psychological support interventions and provided recommendations to enhance these interventions for people with disabilities and their families in the country.To achieve the research objectives, a descriptive analytical approach was employed. A field study was conducted through surveys of families with people with disabilities in the UAE. A purposive non-probability sample of 40 parentes was selected from disability centers in the Ministry of Community Development and Sharjah City for Humanitarian Services.The study results indicated a high degree of utilization of various types of psychological support interventions for people with disabilities and their families in the UAE. This suggests the presence of numerous psychological support interventions, including psychological, social, training, educational, and others, offered to families supporting people with disabilities in the UAE. The interventions involve providing financial and human resources to develop psychological and social support programs, supporting the rights of people with disabilities and their families.The study found that these interventions have a significant positive impact on the overall well-being and quality of life of families. In conclusion, the study proposed several recommendations, including providing necessary financial support to parents to meet the high costs associated with caring for their disabled children, offering essential psychological support to families of people with disabilities, providing needed services for the families of disabled students, such as awareness of proper interaction, and reducing the cost of specialized services for people with disabilities in external centers and institutions.